Pengelolaan Program Pelatihan pada Sanggar Seni Greget Semarang - Sicha Adestiya Silvia Dewi; Mu’arifuddin Mu’arifuddin (Lembaga Pengembangan Kinerja Dosen, 2025)
Training management is a crucial component in organizing training programs and contributes to creating effective training. This study aims to describe the identification of training needs, training methods, training management strategies, and training success indicators at Sanggar Seni Greget in Semarang. The research method employed is descriptive qualitative research. The research subjects include the founder, the head, the secretary, and staff in the field of dance. The research informants consist of an instructor and two training participants. Data collection techniques include interviews, observations, and documentation. Data validity techniques utilize source triangulation and method triangulation. Data analysis encompasses data collection, data reduction, data presentation, and conclusion drawing. The research findings indicate that the identification of training needs at Sanggar Seni Greget involves organizational analysis, job task analysis, and individual analysis. The training methods used are demonstrations, lectures, and simulations. The training management strategy design includes planning, resource management, organizing, training development, promotion, implementation, and evaluation. The success indicators of the training are measured through goal achievement, skill and knowledge enhancement, behavioral changes, participant satisfaction, and productivity.